Penyuluhan Kesehatan Etika Batuk, Bersin dan Cuci Tangan - Susi Rabuana (Lembaga Pengembangan Kinerja Dosen, 2025)
Cough Becomes Non-Physiological When Felt As A Disturbance. Such Cough Is Often A Sign Of Disease In Or Outside The Lungs And Sometimes Is An Early Symptom Of A Disease. Transmission Of Cough Disease Through The Air (Air Borne Infection). The Causes Are Various And Recognition Of The Pathophysiology Of Cough Will Be Very Helpful In Establishing A Diagnosis And Management Of Cough. The purpose of the community service activity is to implement the ethics of coughing, sneezing and washing hands for the community so that the community can live healthily in their households/families. From the results of the counseling activities on Coughing, Sneezing and Washing Hands Ethics, it is hoped that the community will be able to maintain a clean and healthy lifestyle. Always bring a handkerchief or tissue when coughing or sneezing and always wash your hands every day with clean running water